Relação entre engajamento no trabalho e potência de equipes: um estudo em uma instituição do sistema S - Veras, Sabrina Maria Parente (2023)
Companies develop and consolidate themselves in the market, among other factors, through the work done by their employees, therefore, keeping employees engaged promotes better results. Another relevant factor is the use of work teams as a way of optimizing resources. From this perspective, the objective of this study is to investigate the relationship between engagement at work and team strength in an institution of the S System. Engagement is characterized by a positive state of mind towards work, which is based on three dimensions: vigor, dedication and absorption. Team power, on the other hand, refers to a collective belief about the ability of a given team to be effective in carrying out the tasks proposed to it, consisting of two dimensions: productive performance and social relationship. The sample gathers 381 employees of Sesc Ceará distributed in five municipalities of the State who answered an online questionnaire composed of validity scales for the two constructs: engagement and team potency. The research is classified as quantitative, descriptive and survey. Descriptive analyses, Pearson's correlation and simple and multiple regression were performed. The main results indicate a strong relationship between engagement and team potency and high levels of both constructs. It is concluded that the different dimensions of the constructs showed a relationship between weak, moderate and strong, and only the absorption dimension showed a non-significant relationship with the dimensions of team power. The findings contribute to advancing knowledge of the relationship between the two constructs, serving as a stimulus for future studies in companies from different segments.